Hormônios gonadais influenciam nas respostas ventilatórias à hipercapnia em ratos machos e fêmeas wistar adultos - Marques, Danuzia Ambrozio (Universidade Federal de São Carlos, 2014)
Sex hormones may influence many physiological processes. However, it is still unclear whether sex hormones and hormonal fluctuations that occur during the estrous cycle can affect breathing. Our study aimed to evaluate the ventilation (VE), tidal volume (VT), respiratory frequency (fR), oxygen consumption (VO2) ventilatory equivalent (VE/VO2) and body temperature (Tc) of rats at different stages of estrous cycle (proestrus, estrus, metaestrus and diest responses of intact and orchidectomized (ORX) rats to females in estrous phase (when plasma concentrations of estradiol and progesterone are lower) and ovariectomized (OVX) rats during normocapnia and hypercapnia (7% CO2). VE, VT, fR, VO2 and VE/VO2 were not different among animals in different stages of the estrous cycle in normocapnia and hypercapnia. However, Tc was higher in female rats in estrus. Hormone replacement in females did not change the ventilatory and metabolic parameters. Nevertheless, OVX, OVX+E2 and OVX+EP presented lower ventilatory responses to hypercapnia compared to intact females in estrus phase. Intact animals - both males and females in estrus - showed a higher VE and VE/ VO2 in hypercapnia than castrated animals. We also observed that females in estrus had a higher ventilatory response compared to intact male rats. Thus, our data demonstrated that the different phases of the estrous cycle did not change ventilation in normocapnia and hypercapnia. We also observed that gonadectomy reduces the ventilatory response to CO2. Additionally, rats in estrus have higher ventilatory responses to hypercapnia than males.
Keywords: Respiração; Ciclo estral; Hormônios sexuais; Temperatura; Metabolismo; Dimorfismo sexual; Castração; Reposição hormonal; Estrous cycle; Sex hormones; Sexual dimorphism; Breathing; Castration; Hormone replacement; Metabolism; CIENCIAS BIOLOGICAS::FISIOLOGIA